ODS Pseudophakia + Posterior Capsular Opacification (PCO): Case Report - Khilda Safinatin Najiyah; Faozan (PROFESSIONAL HEALTH JOURNAL, 2025)
Posterior capsular opacity (PCO), also known as after cataract, is a complication of cataract surgery that manifests as an opacity that persists or develops after extracapsular lens extraction. 1 The incidence of PCO varies widely in the literature, influenced by the type of intraocular lens (IOL) and patient risk factors. The standard treatment for PCO-related visual impairment is posterior capsulotomy using a neodymium-doped yttrium-aluminum-garnet (Nd: YAG) laser. Although PCO recurrence after initial treatment with YAG capsulotomy is more common in children, it is rare in adults. The underlying pathophysiologic mechanism is analogous to primary PCO, involving proliferation, migration, and/or clustering of lens epithelial cells (LECs), resulting in posterior aperture re-closure. A comprehensive review of recent literature has identified several potential risk factors for PCO recurrence, including younger age, female gender, high myopia, diabetes, vitrectomy status, uveitis, low diopter IOLs, and certain types of IOLs with higher water content.2A 69-year A 69-year-old male with a history of cataract surgery four years ago, a physical examination showing results within normal limits, and an ophthalmologic physical examination showing ODS virus 0.2, PH - NC, arcus senilis +/+, fibrosis type posterior lens opacity +/+, and IOL +/+ was identified. Funduscopic examination revealed a fundus reflex (+/+), diminished due to posterior lens opacities, with a macular reflex that was difficult to assess (+/+) and retinal degeneration (+/+). The diagnosis of ODS pseudophakia + PCO was established based on the patient's history, physical examination results, and supporting examinations of the mother and baby that had been carried out. According to the diagnosis, the patient was administered the primary pharmacological therapy of P Pred ED 6x1 drops in both eyes and the non-pharmacological therapy of Nd: YAG laser treatment in both eyes.